Adenocarcinoma of the Mammary Gland and Its Surgical Excision in a Male Dog – A Case Report - M. Madeena Begum; R. Thangathurai; S. V. Nandhitha; M. Balagangatharathilagar; V. Vijayanand (The Indian Veterinary Journal, 2024)
An eight year old intact male Labrador dog was brought to the hospital with a history of swelling in the caudal abdominal region for the past 3 months and the owner also reported that the mass kept on growing. Physical examination revealed the presence of a hard, painless mass on the right caudal thoracic mammary gland. On clinical examination, all vital parameters were under normal range. On fine needle aspiration cytology the case was diagnosed as mammary gland adenocarcinoma. Pre-operative haemato-biochemical values were under normal range and thoracic radiograph showed no metastasis. Hence, surgery was fixed and a radical excision of right caudal thoracic mammary gland along with the draining lymph node was done. The excised mass was sent for histopathological analysis and the condition was once again confirmed as mammary gland adenocarcinoma. Post-operative care with antibiotics, supportive therapy and wound dressing were followed. Sutures were removed on 7th post-operative day, after the complete healing. Post-operative follow up was done for 3 months and the animal made an uneventful recovery with no recurrence.